Multidisciplinary Approaches Interventions in Prevention of Childhood Obesity: targeted systematic review - Tork, Hanan Mohamed; Boggatz, Thomas (International Journal of Advanced Nursing Studies, 2013)
AbstractAmong children ages 7–19, about 1 in 3 are overweight and obese (BMI-for-age at or above the 85th percentile of the 2000 CDC growth charts.); 32.1% of all boys and 31.3% of all girls are overweight and obese. Because of the dramatic and alarming increase in childhood obesity and its associated health risks, obesity prevention programs targeting children can and should be developed to promote the health of the public. This study is an overview of different interventions conducted, to guide efforts for an effective management of childhood obesity. The aim of this review was to assess the literature regarding the prevention of childhood obesity. Databases that were accessed for current literature included Medline, Cochrane and CINAHL. A total of 26 articles were found based on the inclusion criteria for this study. Only 38% of studies required parents' participation, the sample sizes of the studies varied considerably from 201 to 3135 children. 92% of studies used randomized controlled trials and the range of intervention duration ranged from eight weeks to four years. Implications for future research and practice are presented.